Pengaruh Harga dan Electronic Word of Mouth (E-Wom) terhadap Keputusan Pembelian di Tiktok Shop pada Konsumen Generasi Z Kelurahan Campaka Kota Bandung - Anita Lestari; Ayi Muhiban (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the influence of price and electronic word of mouth (e-WOM) on purchase decisions among Generation Z consumers in Campaka Subdistrict, Bandung City, with a specific focus on the TikTok Shop platform. This research employs a quantitative approach using a survey method by distributing questionnaires to Generation Z consumers in Campaka Subdistrict, Bandung City, with a total of 98 respondents to collect the data. The results of the study indicate that both price and electronic word of mouth have a significant positive effect on purchase decisions among Generation Z consumers in Campaka Subdistrict, Bandung City. Price is generally perceived as good, although aspects related to price suitability based on income levels and purchasing power still show some weaknesses. Similarly, e-WOM activity is considered positive; however, there are still relatively weak aspects regarding the diversity of consumer reviews, as not all respondents actively pay attention to the variation of opinions in reviews. The findings also reveal a significant influence of these variables, where the effect of price on purchase decisions reaches 35.4%, while electronic word of mouth contributes 29.5%, and the combined effect of price and electronic word of mouth on purchase decisions is 64.9%. This study concludes that improvements in price perception and e-WOM can enhance purchase decisions.